2012
DOI: 10.1016/j.ejvs.2012.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities in Incidence, Handling and Outcomes of Patients with Symptomatic and Ruptured Abdominal Aortic Aneurysms in Norway

Abstract: For rAAA, we found substantial geographical variations in incidence, surgery and patient outcome. These results highlight the need for increased awareness about the condition and suggest ways to improve care trajectories to reduce delay to surgery, thereby minimising rupture mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Whereas elective surgery has a mortality usually reported <4%, 2,3 a ruptured infrarenal AAA (rAAA) represents a lifethreatening emergency with mortality reported between 30% and 50% in those undergoing repair. [4][5][6] Indeed, a recent study comparing outcomes of rAAA in the United States and England reported an overall in-hospital mortality as high as 65%, 7 with notable differences between the countries. Although the mortality from rAAA remains high, some reports suggest a decline in the rates of rAAA, 4,5 although the exact degree of decline and its contributing factors remain unclear.…”
mentioning
confidence: 96%
“…Whereas elective surgery has a mortality usually reported <4%, 2,3 a ruptured infrarenal AAA (rAAA) represents a lifethreatening emergency with mortality reported between 30% and 50% in those undergoing repair. [4][5][6] Indeed, a recent study comparing outcomes of rAAA in the United States and England reported an overall in-hospital mortality as high as 65%, 7 with notable differences between the countries. Although the mortality from rAAA remains high, some reports suggest a decline in the rates of rAAA, 4,5 although the exact degree of decline and its contributing factors remain unclear.…”
mentioning
confidence: 96%
“…Scholarly articles report that the population most likely to show decreased incidence of AAA are those who might have benefited most from lower smoking rates and increased overall penetrance of statins (1,3,7). However, it is crucial to consider, first, that the use of endovascular repair for rAAA increased from 13% in 2002 to 73% in 2013; and second, that the demographic trend has been moving toward an increasing incidence and prevalence of cardiovascular disease in elderly men (4,8). In some reports, the mean age was 70-75 years, with over 78-90% of the patients being men (7,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Immediate diagnosis and rapid treatment are critical. Despite advances in surgery and endovascular repair, the mortality rate for rAAA surgery is as high as 30-50% (4,5). Emergency EVAR is an alternative in patients with rAAA (5).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of institutions have initiated protocols for endovascular repair of rAAA with promising results in small series, but not all institutions are equipped to treat rAAA using minimally invasive technology. The transfer of patients with rAAA can be associated with a high mortality (17 to 19%) in comparison with those undergoing repair at the institution in which minimally invasive technology is available 2,[3][4][5] .…”
Section: Introductionmentioning
confidence: 99%